REPRODUCTIVE BIOLOGY OF STRIPED SNAKEHEAD (Channa striata Bloch, 1973) IN BOGOR AND BEKASI, WEST JAVA - Adang Saputra; Muhamad Hunaina Fariduddin Ath-thar; Reza Samsudin; Fera Permata Putri; Vitas Atmadi Prakoso (BERITA BIOLOGI, 2017)
Striped snakehead is one of the potential local species, however, its production in Indonesia still comes from capture fisheries. Over exploitation had decrease the population in nature. Domestication is one of promising tool to solve the problems faced. In order to breed the domesticated species, the information of their reproduction was needed. This study aimed to describe relationship between length and weight, length and fecundity, weight – fecundity and gonad weight – fecundity of the striped snakehead from West Java. A total of 19 mature female specimens were collected from Parung (Bogor), and seven mature female specimens were collected from Babelan (Bekasi). The results showed that the determinant value (R2), the first for Parung and the second for Babelan, between weight and fecundity were 0.599 and 0.843, length-fecundity were 0.541 and 0.841; gonad weight – fecundity 1.00 and 0.846 Gonadosomatic Index (GSI) ranged from 0.67 to 9.94% and 2.03 to 8.17%. Gonad Index ranged from 6.17 – 76.73 and 18.48 – 76.77, respectively. The data indicated that growth pattern was allometric. Length and body weight has linear relationship with gonads and fecundity. Fecundity has higher correlation to the weight rather than length. Gonad weight and fecundity has a strong relationship.